A Pilot Study of Four Phonetic Changes in General British - Bikelienė, Lina; Černelytė, Laura (Verbum, 2020)
The pilot study reports on the prevalence of four phonetic changes (yod coalescence, yod dropping, /ʒ/ versus /ʤ/ in loan words, and GOAT allophony) in General British. The study consists of two stages to address the question from different perspectives: native speakers’ preferences and documentation of the changes in current pronouncing dictionaries.Sixty words likely to undergo one of the changes are chosen for the analysis. The survey is based on the framework by Wells (1998). Though the descriptive study resultsreveal a high degree of the respondents’ preference for ‘modern’ pronunciation, it varies across categories. The comparative analysis of the manifestation of the changes in the Longman Pronunciation Dictionary (2008), the Cambridge English Pronouncing Dictionary (2011), and the Current British English Searchable Transcriptions (N/A) indicate their gradual way into the ‘standard’ language.